PROBLEMATICS OF LIMITING THE QUANTITY OF VILLAGE HEAD CANDIDATES BASED ON THE PROVISIONS OF ARTICLE 23 PARAGRAPH 1 OF THE REGULATION OF THE MINISTER OF HOME AFFAIRS NUMBER 112 OF 2014 CONCERNING VILLAGE HEAD ELECTIONS - Sihombing, Rizky Darmawansyah; Nasution, Mirza; NAM Sihombing, Eka (NOMOI Law Review, 2025)
Village Head Election in Indonesia still has several problems. Not only at the application level, but also from the regulation still has problems. The limitation of the quantity of Village Head candidates will not be found in Law No. 6 of 2014 concerning Villages, but the regulation related to this limitation can be found in its derivative regulations, namely Government Regulation Number 43 of 2014 concerning Implementing Regulations of Law Number 6 of 2014 concerning Villages and Regulation of the Minister of Home Affairs Number 112 of 2014 concerning Village Head Elections. So that with the limitation regulations regulated in the derivative regulations of Law No. 6 of 2014, there is a potential for a conflict of norms between the Law and the PP. thus causing legal uncertainty regarding the number of village head candidates. This study uses a normative legal research method with a statutory regulatory approach. The results of this study indicate that in the provisions of Law No. 6 of 2014 concerning Village Heads, especially in the section on the requirements for Village Head candidates, there are no regulations related to the limitation of the quantity of Village Head candidates. So this regulation opens up opportunities for village communities who are declared to meet the requirements to be able to participate in the village head election. The regulation relating to the limitation of the number of village head candidates as regulated in the derivative regulation of Law No. 6 of 2014 concerning villages can be categorized as contradictory and inconsistent with the principle of lex superior derogate legi inferiori because Law No. 6 of 2014 as its main regulation does not provide a limit on the maximum number of village head candidates .